2021
DOI: 10.1007/s00404-020-05921-8
|View full text |Cite
|
Sign up to set email alerts
|

CD34 and Bcl-2 as predictors for the efficacy of neoadjuvant chemotherapy in cervical cancer

Abstract: Background Successful neoadjuvant chemotherapy (NACT) could improve the surgical resection rate and radical curability of patients with cervical cancer, but only a subset of patients benefits. Therefore, identifying predictive biomarkers are urgently needed. The aim of this study was to evaluate the predictive value of CD34 and Bcl-2 in the NACT effectiveness of cervical cancer. Methods Sixty-seven patients with locally advanced cervical cancer (FIGO stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Its coded products can bind to the corresponding kinases, thus promoting the development of cell cycle and enhancing cell vitality 19 . Bcl-2 is an apoptosis-inhibiting gene, which plays a role by antagonizing the apoptosis-promoting gene Bax 20 . Caspase-3 is a pro-apoptosis gene, which is activated by the mitochondrial and death receptor pathways, and then causes cell apoptosis 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Its coded products can bind to the corresponding kinases, thus promoting the development of cell cycle and enhancing cell vitality 19 . Bcl-2 is an apoptosis-inhibiting gene, which plays a role by antagonizing the apoptosis-promoting gene Bax 20 . Caspase-3 is a pro-apoptosis gene, which is activated by the mitochondrial and death receptor pathways, and then causes cell apoptosis 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Authors consider that high expression of CD34 signifies the presence of an anomalous vessel pattern and disturbing tumor vasculature is one of the primary strategies in cancer chemotherapy. Moreover, this marker has an important diagnostic and prognostic value -the decrease of CD34 expression after therapy correlates with its effectiveness [21].…”
Section: Discussionmentioning
confidence: 99%
“…Microsatellite instability -high (MSI-H), programmed cell death ligand 1 (PD-L1) expression, and high tumor mutational burden (TMB) are the most actively investigated biomarkers (8). Other factors with antitumor activity (e.g., microRNAs, B-cell lymphoma-2 (Bcl-2), and C-kit) were also investigated in preclinical studies; however, those factors were not found to be good predictors of the effect of immunotherapy at this time (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%